Equipment and technologies for the production and use of nanostructured materials - P. A. Vityaz; Yu. A. Nikalaichyk; S. L. Rovin; N. A. Svidunovich; D. V. Kuis (Литьë и металлургия, 2021)
This article is a continuation of the series devoted to the creation and application of nanomaterials and nanotechnologies in modern industry in general and in metallurgy, materials science and foundry production in particular. The article deals with the choice of equipment and the development of effective methods for obtaining nanomaterials. Examples of the application of the developed equipment, technologies and materials obtained in the Republic of Belarus and abroad are given.